1999
DOI: 10.1164/ajrccm.160.5.9902085
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of the Forced Oscillation Technique for CPAP Titration in the Sleep Apnea/Hypopnea Syndrome

Abstract: We have previously demonstrated that upper airway obstruction in sleep apnea/hypopnea syndrome (SAHS) can be accurately assessed in real-time by measuring respiratory impedance (|Z|) with the forced oscillation technique (FOT). The aims of the present study were: (1) to determine the feasibility of identifying the optimal continuous positive airway pressure (CPAP) for patients with SAHS based on analysis of the |Z| signal during conventional polysomnographic CPAP titration studies; and (2) to evaluate practica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
36
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 15 publications
4
36
0
Order By: Relevance
“…Frequency analysis of the EEG signal was carried out and no evidence of neurological activation was found. These findings are consistent with the clinical experience with FOT [3][4][5]. Significant effects on the upper airway or the EEG produced by the use of FOT, with and without CPAP, were not observed in subjects with SAHS.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Frequency analysis of the EEG signal was carried out and no evidence of neurological activation was found. These findings are consistent with the clinical experience with FOT [3][4][5]. Significant effects on the upper airway or the EEG produced by the use of FOT, with and without CPAP, were not observed in subjects with SAHS.…”
Section: Discussionsupporting
confidence: 89%
“…13 The forced oscillation technique (FOT) is a simple and noninvasive method that allows continuous online monitoring of airflow obstruction during sleep, even in the absence of flow, as occurs in apnoeas. FOT has been applied in clinical diagnostic studies in patients with sleep apnoea/hypopnoea syndrome (SAHS) [1][2][3][4] and in continuous positive airway pressure (CPAP) titration studies [5,6] with highly encouraging results.…”
mentioning
confidence: 99%
“…Previous studies in patients with OSA have indicated that major upper airway narrowing or collapse can be reliably identified when the impedance value increases to levels more than twice baseline values during tidal breathing [16,27]. Therefore, for the various categories of respiratory events we determined the proportion of events for which |Z| exceeded this value.…”
Section: Measurements Of Impedance Values |Z| During Apnoeas and Hypomentioning
confidence: 99%
“…The forced oscillation technique (FOT) is a noninvasive method for instantaneous measurement of respiratory system mechanics which has been shown to be reliable in assessing upper airway calibre during sleep in patients with obstructive sleep apnoea (OSA) [16][17][18]. FOT systems have been developed which measure impedance (|Z| cmH 2 O?s?L -1 ) of the respiratory system during sleep in a continuous fashion without disturbing sleep architecture or altering upper airway muscle tone [19].…”
mentioning
confidence: 99%
See 1 more Smart Citation